Do Manual and Voxel-Based Morphometry Measure the Same? A Proof of Concept Study - Focke, Niels K.; Trost, Sarah; Paulus, Walter; Falkai, Peter; Gruber, Oliver (Frontiers in Psychiatry, 2014)
Voxel-based morphometry (VBM) is a commonly used method to study volumetric variations on a whole brain basis. However it is often criticised for potential confounds, mainly based on imperfect spatial registration. We therefore aimed to evaluate if VBM and “gold-standard” manual volumetry are measuring the same effects with respect to subcortical grey matter volumes. Manual regions-of-interest (ROIs) were drawn in the hippocampus, amygdala, nucleus accumbens, thalamus, putamen, pallidum and caudate nucleus bilaterally. Resulting volumes were used for a whole brain VBM correlation analysis with SPM8. The hippocampus, amygdala, putamen and caudate nucleus were correctly identified by SPM using the contemporary high-dimensional normalization (DARTEL toolbox). This strongly suggests that VBM and manual volumetry both are indeed measuring the same effects with regard to subcortical brain structures.